God's Design for the Church : a guide for African pastors and ministry leaders - Mbewe, Conrad (Wheaton, Illinois : Crossway, 2020)
"A survey of biblical teaching regarding the church, written for African pastors and ministry leaders"--
Includes bibliographical references and index.
Keywords: Christianity -- Africa; Church; Church -- Biblical teaching